2010
DOI: 10.1176/ps.2010.61.7.684
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Dropout From Psychotherapy for Depression in Community Practice

Abstract: Early dropout from psychotherapy for depression was only weakly related to consumers' demographic characteristics. Dropout rates were lower among those with more severe depression, but a significant number of persons with moderate or severe symptoms of depression still discontinued treatment before the second visit. Allocation of visits for individual consumers was markedly different for group- and network-model psychotherapists, but these data did not allow for examination of differences in outcomes for those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 27 publications
0
53
1
4
Order By: Relevance
“…Indeed, in the larger psychotherapy literature, it is very common for adults who begin a course of psychotherapy to fail to return for a second visit (Hamilton, Moore, Crane, & Payne, 2011; Simon, Imel, Ludman, & Steinfeld, 2012; Simon & Ludman, 2010). Most of the interventions developed for those with comorbid PTSD/AD population are quite lengthy, which can be challenging with such high drop-out rates.…”
Section: Overview Of Psychotherapy For Comorbid Ptsd and Alcohol And mentioning
confidence: 99%
“…Indeed, in the larger psychotherapy literature, it is very common for adults who begin a course of psychotherapy to fail to return for a second visit (Hamilton, Moore, Crane, & Payne, 2011; Simon, Imel, Ludman, & Steinfeld, 2012; Simon & Ludman, 2010). Most of the interventions developed for those with comorbid PTSD/AD population are quite lengthy, which can be challenging with such high drop-out rates.…”
Section: Overview Of Psychotherapy For Comorbid Ptsd and Alcohol And mentioning
confidence: 99%
“…Community studies have reported that 22% (Simon & Ludman, 2010) to 34% (Miranda et al, 2003) of people referred do not attend an initial or intake session. Across multiple settings, the modal number of sessions attended by patients is one (Phillips, 1985), with 21%–49% of individuals not attending therapy after their initial intake (Garfield, 1994; Simon & Ludman, 2010). Potential reasons for not returning include feeling better, being dissatisfied with treatment, and wanting to solve problems independently.…”
mentioning
confidence: 99%
“…Our previous research (Simon & Ludman, 2010) also suggested large differences in patterns of dropout between psychotherapy provided by salaried, clinic-based (group model) therapists and that provided by independent contracted (network model) therapists. Risk of dropout prior to the first visit was significantly higher for network model therapists while risk of dropout between the first and second visits was significantly higher for group model therapists.…”
mentioning
confidence: 81%
“…Zivin and colleagues reported that 15% of members calling to request services from a university-based managed mental health care organization did not attend an initial visit within 90 days (Zivin, et al, 2009). Our previous research in a small sample of health plan members found that almost 25% of adults calling to request psychotherapy for depression did not attend an initial visit (Simon & Ludman, 2010). …”
mentioning
confidence: 99%